2013
DOI: 10.1002/anie.201309426
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Imidazolate Metal–Organic Frameworks Photosplit CO2 under Mild Reaction Conditions

Abstract: Metal-organic frameworks (MOFs) have shown great promise for CO2 capture and storage. However, the operation of chemical redox functions of framework substances and organic CO2 -trapping entities which are spatially linked together to catalyze CO2 conversion has had much less attention. Reported herein is a cobalt-containing zeolitic imidazolate framework (Co-ZIF-9) which serves as a robust MOF cocatalyst to reduce CO2 by cooperating with a ruthenium-based photosensitizer. The catalytic turnover number of Co-Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
313
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(327 citation statements)
references
References 66 publications
(15 reference statements)
9
313
0
5
Order By: Relevance
“…Although still in the early stage of exploration, ZIFs have been used as photocatalysts for dye and phenol degradation as well as CO2 reduction. 15,[17][18][19] In these systems, photoactive nanostructures/molecules are incorporated into the highly porous structure of ZIFs, where ZIFs are used as a simple host or passive medium for dispersing the catalytic active species. This strategy has been widely used in developing zeolite-based photocatalysts 20 and recently in preparing MOF/nanocomposite or MOF/molecular catalyst hybrids, 19,21,22 yet suffers from challenges, notably the difficulty in preventing the guest material aggregation and the lack of the control over spatial distribution and homogeneity.…”
mentioning
confidence: 99%
“…Although still in the early stage of exploration, ZIFs have been used as photocatalysts for dye and phenol degradation as well as CO2 reduction. 15,[17][18][19] In these systems, photoactive nanostructures/molecules are incorporated into the highly porous structure of ZIFs, where ZIFs are used as a simple host or passive medium for dispersing the catalytic active species. This strategy has been widely used in developing zeolite-based photocatalysts 20 and recently in preparing MOF/nanocomposite or MOF/molecular catalyst hybrids, 19,21,22 yet suffers from challenges, notably the difficulty in preventing the guest material aggregation and the lack of the control over spatial distribution and homogeneity.…”
mentioning
confidence: 99%
“…Co-ZIF-9 was first used as ac atalyst for photocatalytic CO 2 reduction by Wang et al in 2014. [37] They reported that the MOFs exhibited not only gas absorption properties, but also CO 2 reduction activity under photochemical conditions. Ah eterogeneouss ystem composedo fC o-ZIF-9 as catalyst, P1 as PS, and TEOA as SED in aC O 2 -saturated CH 3 CN/H 2 O solventmixture produced CO and H 2 under visible light irradiation.…”
Section: Cobalt-based Mofsmentioning
confidence: 99%
“…Interestingly, such 2D layer parallels to the equivalent one with a interleaving, resulting in a rare bilayer structure extending along the ac plane (Figure 3c,d). From the topological view [43], if the Zn centres are considered as nodes and the 5-HO-1,3-BDC and bpmb ligands are considered as linkers, the bilayer structure of 2 can be specified by a Schläfli symbol of 4 4 …”
Section: Crystal Structure Ofmentioning
confidence: 99%
“…Topologically, the overall structure of 4 can be described as a pcu net with the six-connected 4 12 6 3 topology (Figure 5d). 4 ] unit serves as a four-fold node, which links four equivalent ones via sharing of four ADB ligands to form a 2D wrinkled network extending along the bc plane (Figure 5b). Furthermore, the bpmb ligands are employed as linkers (pink) to bridge the 2D networks producing a 3D framework (Figure 5c).…”
Section: Crystal Structure Ofmentioning
confidence: 99%
See 1 more Smart Citation